Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan: Penilaian Kinerja Menggunakan Key Performance Indicator - Ayu Try Handayani W; Zainal Abidin Umar; Rezkiawan Tantawi (Economic Reviews Journal, 2024)
This research aims to find out: 1) How the influence of work environment on employee performance at PT ARBA Group Gorontalo, 2) How the influence of work discipline on employee performance at PT ARBA Group Gorontalo, and 3) How the influence of work environment and work discipline on employee performance at PT ARBA Group Gorontalo. With 35 respondents determined using saturated sampling method. The approach in this study uses a quantitative approach with data collection techniques using a questionnaire (questionnaire). Data analysis techniques using multiple linear regression. Based on the results of the analysis it was found that: 1) Partially, the work environment has a significant effect on employee performance with t count> t table, namely 2.718> 2.036. 2) Work discipline has a significant effect on employee performance with t count> t table, namely 4,770> 2,036 and 3) Simultaneously the work environment and work discipline have a significant effect on employee performance at PT. ARBA Group Gorontalo with f count> f table, namely 38,140> 3,284. With a coefficient determination value of work environment and work discipline of 0.686 or 68.8% strong effect on employee performance at PT. ARBA Group Gorontalo. While 0.314 or 31.4% is influenced by other variables not explained in this study.